Parity and BMI (Body Mass Index) that Related with Myoma Uteri in Women of Childbearing Age - Miftachu Jannah; Ni Ketut Alit; Aria Aulia (Universitas Airlangga, 2016)
Introduction : Uterine myomas are benign tumors of uterine smooth muscle cells are composed of smooth muscletissue, connective tissue and collagen fibroids. In Indonesia myoma uteri was found 2.39% - 11.7% of all gynecologicalpatients treated. The exact cause of uterine myoma is had known for certain until today. Risk factors such as age ofmenarche, family history, body mass index (BMI), parity and type of contraception can cause uterine myoma. Thisstudy aims to determine the factors correlating with the incidence of uterine myomas in women of childbearing age in PolyGynecology, dr.Mohamad Soewandhi Hospital, Surabaya. Method : This research used a case control design.Populations were all women who visit to Poly Gynecology. It used purposive sampling technique. Total sampel were 30patients with myoma uteri and 30 women of childbearing age. The independent variable was the age of menarche, familyhistory, BMI, parity, type of contraception and the dependent variable was the incidence of uterine myoma. Data werecollected by interviews, weight scales, height measurement and medical records. The analysis used Chi Square / Fisher'sExact Test with level of significance of £ 0,05. Result : The results showed that age of menarche (p = 0.158) and familyhistory (p = 0.100) had no correlation with myoma uteri. Body Mass Index (p = 0.009), parity (p = 0.00) and type ofcontraception (p = 0.00) had correlation with myoma uteri. Discussion : Every woman more aware about the disease ofreproductive age, especially myoma uteri by reducing foods that contain estrogen such as meat and beans.